THE INFLUENCE OF GREEN ADVERTISING AND BRAND IMAGE ON PURCHASE DECISIONS AND THEIR IMPACT ON CUSTOMER LOYALTY CHIYODA LED LIGHTS (Case Study in Cisaranten Kidul Village) - Adang Sutisna (Jurnal Ekonomi, 2022)
Every customer who is loyal to a product has factors in deciding to buy. This can happen when deciding to use a product, such as a Lamp. Along with the green movement around the world to make people aware of their care for the environment, so many companies advertise their products with environmental themes or what is called Green Advertising, this makes light consumers switch to using LED lights. Brand Image is a perception of a brand that has an impact on a customer's purchase decision. Based on the description above, the writer is interested in conducting a research in the form of a thesis with the title "The Effect of Green Advertising, and Brand Image on Purchase Decisions and their impact on Customer Loyalty of Chiyoda LED Lights. The method used in this research is descriptive analysis with survey method, the data obtained and used in this research are primary data and secondary data. Data collection technique in this research is by distributing questionnaires. The sample taken in this study amounted to 70 respondents who are loyal consumers of Chiyoda LED lamps who are domiciled in the Cisaranten Kidul sub-district area. In conducting this research, four variables were used, namely Green Advertising (X1), Brand Image (X2), Purchase Decision (Y), and Customer Loyalty (Z). The results of the study using multiple regression analysis, it is proven that Green Advertising, and Brand Image through Purchase Decisions have a significant effect on customer loyalty, either partially or simultaneously. Then in the analysis of the coefficient of determination, it can be seen that the Purchase Decision is influenced by Green Advertising, Brand Image, and Purchase Decision by 65.1%, and the rest is influenced by other factors